DESIGN OF METAL DETECTION EQUIPMENT USING MAGNETIC WAVES GENERATION - Muhamad Abidin; Fivtatianti H., SKom., MM Fivtatianti H., SKom., MM (Jurnal Sistem Komputer, 2005)
In this paper discussed about a tool that can be used as a tracer sharp weapon. Thisdetector can detect the presence of a sharp weapon that was hidden by the visitorcenter shopping. This detector uses magnetic waves as a means of detection and thesearch coil as a sensor.Because the use of magnetic waves, hence this detector has a lot of deficienciesranging from its unknowable metals which can not be detected until detected. Electricfield strength also has a huge influence on the detector. Electric field strength candisrupt the signal emitted by the search coil so that search can not catch the signalsreflected back by the metal.